SURVEI TINGKAT KONSENTRASI DAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DENGAN MEDIA WORDWALL - Sabrina Aulia Rahma; Linda Zakiah; M. Syarif Sumantri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Motivation ist he power, need, enthusiasm, pressure, or psychological mechanism that drives a person or group of people. Encourages a person or group of people to achieve certain achievements according to their own desires. Concentration is the concentration of mind and focus on something. Wordwall learning media is a technology-based digital application to support learning. The purpose of this study was to determine and describe the level of motivation and concentration of students in the use of wordwall as an Indonesian language learning media. The results of this study were obtained with 55% of students very good level of concentration and motivation in the use of wordwall application. This is in line with the purpose of this study which is to increase students’ motivation and concentration in learning.